Clinical significance of signal regulatory protein alpha (SIRPα) expression in esophageal squamous cell carcinoma. Issue 8 (11th June 2021) - Koga, Naomichi; Hu, Qingjiang; Sakai, Akihiro; Takada, Kazuki; Nakanishi, Ryota; Hisamatsu, Yuichi; Ando, Koji; Kimura, Yasue; Oki, Eiji; Oda, Yoshinao; Mori, Masaki
Abstract: Signal regulatory protein alpha (SIRPα) is a type I transmembrane protein that inhibits macrophage phagocytosis of tumor cells upon interaction with CD47, and the CD47‐SIRPα pathway acts as an immune checkpoint factor in cancers. This study aims to clarify the clinical significance of SIRPα expression in esophageal squamous cell carcinoma (ESCC). First, we assessed SIRPα expression using RNA sequencing data of 95 ESCC tissues from The Cancer Genome Atlas (TCGA) and immunohistochemical analytic data from our cohort of 131 patients with ESCC. Next, we investigated the correlation of SIRPα expression with clinicopathological factors, patient survival, infiltration of tumor immune cells, and expression of programmed cell death‐ligand 1 (PD‐L1). Overall survival was significantly poorer with high SIRPα expression than with low expression in both TCGA and our patient cohort ( P  < .001 and P  = .027, respectively). High SIRPα expression was associated with greater depth of tumor invasion ( P  = .0017). Expression of SIRPα was also significantly correlated with the tumor infiltration of M1 macrophages, M2 macrophages, CD8 + T cells, and PD‐L1 expression ( P  < .001, P  < .001, P  = .03, and P  < .001, respectively). Moreover, patients with SIRPα/PD‐L1 coexpression tended to have a worse prognosis than patients with expression of either protein alone or neither. Taken together, SIRPα indicates poor prognosis in ESCC, possibly through inhibiting macrophage phagocytosis of tumor cells and inducing suppression of antitumor immunity. Signal regulatory protein alpha should be considered as a potential therapeutic target in ESCC, especially if combined with PD‐1‐PD‐L1 blockade. Abstract : This article highlights the clinical significance of signal regulatory protein alpha (SIRPα) in esophageal squamous cell carcinoma (ESCC). The results showed that high SIRPα expression was a significant indicator of poor prognosis in ESCC and SIRPα/programmed cell death‐ligand 1 (PD‐L1) coexpression had a negative synergistic impact on prognosis in ESCC. Thus, SIRPα could be a novel clinical biomarker and a potential therapeutic target in ESCC, especially if combined with PD‐1‐PD‐L1 blockade.